Formulasi dan uji stabilitas sediaan lulur dari rimpang kunyit (Curcuma longa linn) - Rani Prabandari (Viva Medika, 2018)
ABSTRACT Lulur is a type of cosmetics made from flowers and other plant ingredients that are very useful for maintaining beauty, health, smoothness and brightness of the skin of the body. Lulur can help clean the dirt that sticks to the skin due to the influence of weather and pollution factors so that the skin becomes healthy, clean and beautiful. The contents of the substance include turmeric: curcuminoid which consists of curcumin, desmetoksikumin and bisdesmetoksikurkumin and other beneficial substances, such as volatile essential oils of oil, fat, carbohydrates, protein, starch, vitamin C, iron, phosphorus, and calcium. Curcumin is a yellow substance contained by turmeric, on average 10.29%, has broad spectrum biological activity including antihepototoxic, antibacterial and antioxidant so that turmeric is able to be used for traditional medicine both to maintain health and skin beauty of the body, The method used is study experimental scrubs and tested the stability of scrubs containing turmeric rhizome powder. The best scrubs are formula 1 which uses the ratio of turmeric powder to light brown scrub, homogeneous and perfectly fused body scrub, has a pH of 5, spread of 10,321 cm2, has a viscosity consistency of 99,000 mPa.s and adhesion for 4 seconds. Keywords: formulations, scrubs, turmeric.